2020
DOI: 10.1108/ccsm-03-2019-0055
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical foundations of antecedents of internationalization and moderators in multinationality–performance relationship

Abstract: PurposeIn this paper, the authors undertake a systematic analysis of multinationality–performance (M-P) literature published in the last decade, when antecedents for internationalization and moderators of the M-P relationship had attained a center stage in international business and international management research. Though M-P relationship is one of the most widely studied topics within international business literature, so far synthesis of the entire theoretical landscape is missing in extant literature.Desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 198 publications
(196 reference statements)
0
12
0
Order By: Relevance
“…The relationship between internationalization and performance has been widely studied in international strategy literature for almost 50 years (Hitt et al, 2006;Nguyen & Kim, 2020;Purkayastha et al, 2020). Both the initial studies and the following ones have provided inconsistent findings on the linear relationship or curvilinear relationships between internationalization and the performance level of firms in different contexts (Brewer, 1981;Grant, 1987;Lu & Beamish, 2004;Ruigrok & Wagner, 2003).…”
Section: Extended Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between internationalization and performance has been widely studied in international strategy literature for almost 50 years (Hitt et al, 2006;Nguyen & Kim, 2020;Purkayastha et al, 2020). Both the initial studies and the following ones have provided inconsistent findings on the linear relationship or curvilinear relationships between internationalization and the performance level of firms in different contexts (Brewer, 1981;Grant, 1987;Lu & Beamish, 2004;Ruigrok & Wagner, 2003).…”
Section: Extended Summarymentioning
confidence: 99%
“…Relatedly, these findings generally were tested in advanced country contexts that have corporations with better tangible and intangible resources and capabilities. The research about how emerging country corporations perform after their internationalization attempts still needs to be investigated in different contexts (Purkayastha et al, 2020). Although internationalization provides advantages like economies of scale and decreased market imperfections in the product, factor, and financial markets (Buckley & Casson, 1976;Dunning, 1998;Ruigrok & Wagner, 2003), firms have to deal with increased transaction costs and liability of foreignness (Lu & Beamish, 2004;Williamson, 1979;Zaheer, 1995) due to operating in institutionally and culturally distant countries.…”
Section: Extended Summarymentioning
confidence: 99%
“…Although market analysis is even more relevant for internationalization into emerging markets, few studies are focused on this topic (Caiazza, 2012, 2014, 2016), particularly in Africa (Oguji and Owusu, 2017). Through a systematic analysis of literature, Purkayastha et al (2020) found that research on internationalization in the last decade was dominated by theory testing in the context of developed economies. The authors highlighted a rich research potential in the context of emerging markets.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, we must highlight that extant literature offers no extensive study on the role of motives as a contextual variable (Li, 2007;Nguyen, 2011;Ruigrok & Wagner, 2004;Verbeke & Brugman, 2009;Verbeke & Forootan, 2012). While a number of factors associated with the international organisational structure of firms is used as explanatory variables, an investigation of strategic moderating factors remains mostly absent (Purkayastha et al, 2020). Jain and Prakash (2016) find a negative moderation of the MP relationship for the predominance of labour-seeking motives as opposed to market-seeking motives among Indian software firms.…”
Section: Introductionmentioning
confidence: 97%
“…Despite a growing body of empirical research, the findings on the MP linkage remain inconsistent (Verbeke, Li, & Goerzen, 2009) and often described as contradictory or confusing (Nguyen & Kim, 2020). Some scholars attribute this situation to methodological limitations of extant research and call for a more in-depth exploration of contextual variables (Purkayastha, Sharma, & Karna, 2020;Tallman & Pedersen, 2012).…”
Section: Introductionmentioning
confidence: 99%